2017
DOI: 10.1002/ejsp.2317
|View full text |Cite
|
Sign up to set email alerts
|

Fighting ageism through nostalgia

Abstract: Two experiments tested whether nostalgia is as a resource for fighting ageism. In Experiment 1, younger adults who recalled a nostalgic (vs. ordinary) encounter with an older adult showed a more positive attitude toward older adults, mediated by greater inclusion of older adults in the self (inclusion of outgroup in the self; IOGS). In Experiment 2, these findings were replicated and extended with a subtle nostalgia manipulation. Younger adults identified an older, familiar adult. Then, they wrote about an enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 87 publications
2
30
0
Order By: Relevance
“…The train has left the station on the demographic reality: Little can be done about slowing the pace of population aging or increasing the fertility rate that remains stubbornly low in many developed countries. Instead, cultural mindsets are more malleable, as priming studies have shown, and individual-level interventions to decrease interpersonal ageism have achieved considerable success ( Lytle et al, 2020 ; Turner et al, 2018 ). Additionally, priming with implicit age stereotypes has been shown to effectively increase the physical performance of older adults ( Levy et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The train has left the station on the demographic reality: Little can be done about slowing the pace of population aging or increasing the fertility rate that remains stubbornly low in many developed countries. Instead, cultural mindsets are more malleable, as priming studies have shown, and individual-level interventions to decrease interpersonal ageism have achieved considerable success ( Lytle et al, 2020 ; Turner et al, 2018 ). Additionally, priming with implicit age stereotypes has been shown to effectively increase the physical performance of older adults ( Levy et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, collective nostalgia may also serve to benefit intergroup relations. For example, Turner et al (2018) found that nostalgic memory that is focused on shared experience with an outgroup member yields reduced prejudice towards the outgroup. Additionally, research has shown that some Americans report high levels of nostalgia for the 1960s, a decade known for its openness and freedom (Wilson, 2005).…”
Section: The Malleability Of Collective Memorymentioning
confidence: 99%
“…Other studies (e.g., Cheung et al, 2017;Smeekes et al, 2015) have used items that directly mention nostalgia for the ingroup's past, but still only assess the extent to which the group-based emotion is experienced as a whole (e.g., "When thinking about [the ingroup], to what extent do you feel nostalgic about the way [ingroup members] were in the past"). Even in Turner et al (2018) where the researchers focused participants' attention on a specific aspect of the ingroup's past (i.e., a shared past with an outgroup), they were simply asked if they "feel nostalgic at the moment".…”
Section: Why We Need To Focus On Collective Nostalgia Contentmentioning
confidence: 99%
“…First, it is important to distinguish between nostalgia for experiences from one's personal past (i.e., the focus of our present studies) and nostalgia for the ostensibly glorious past of one's group (e.g., national nostalgia). Proneness to nostalgia for one's personal past is negatively correlated with prejudice against outgroups (Smeekes, 2015;Cheung et al, 2017a), and recalling a personally nostalgic (compared to ordinary) experience with a specific outgroup member reduces prejudice toward the entire outgroup (Turner et al, 2012(Turner et al, , 2013(Turner et al, , 2018. By contrast, nostalgia for the past of one's group (e.g., "How often do you long for the good old days of the country?")…”
Section: Limitations and Future Directionsmentioning
confidence: 99%